Phenetic Characterization of Nitrogen Fixing Azotobacter from Rhizospheric Soil of Southern Rajasthan - Devendra Jain; Gunnjeet Kaur; Ali Asger Bhojiya; Surya Chauhan; S.K. Khandelwal; R.H. Meena; Deepak Rajpurohit; Santosh Ranjan Mohanty (Journal of Pure and Applied Microbiology, 2021)
The present research was conducted to characterize the indigenous plant growth promoting (PGP) Azotobacter strains isolated from plant root interface of semi-arid regions of Rajasthan (India) and to study their potential to be used as bio-fertilizers. A total of 172 Azotobacter strains were isolated, purified and based on the morphological test i.e. gram staining, pigmentation, cyst formation, fluorescence etc, broadly classified as Azotobacter. Further the secluded strains were examined for biochemical analysis and plant growth promoting characters. All the isolates showed different biochemical characteristics and significant PGP traits. IAA activity of the Azotobacter strains ranges from 54.5-6000 µg/mL. Ammonia, HCN and siderophore was produced by 92.4%, 78.4% and 80.23% of the total isolates respectively. Solubilization of phosphate was observed in 97.6% of the total isolates. These strains were also characterized for qualitative and quantitative N2 fixation abilities and the result indicated that 114 strains showed positive results on nitrogen free malate agar medium (NFMM) containing bromothymol blue (BTB) and able to produce 18.93-475.6 N-moles C2H4 mg protein−1 h−1 of acetylene reduced by Azotobacter strains. In vitro pot studies revealed that the selected native Azotobacter strains having high ARA results significantly increase the plant growth characters. Shoot length, root length, root number and chlorophyll content and leaf number increases by 45.62%, 17.60%, 97.49%, 49.69% and 27.83% respectively in pot inoculated with AZO23-3 as compared to control. These effective strains can further be utilized for development of effective microbial formulations.